The Non-Duality of the “Conditioned” and “Unconditioned”: Hongzhou Chan Buddhism on Reconciling the Morality/Prudence Distinction - Jacob Bender (Religions)
This paper illustrates how Hongzhou Chan Buddhism provides valuable resources for dealing with issues in contemporary moral philosophy. In particular, when philosophers adopt the Hongzhou Chan Buddhist’s non-dualistic account of reality, we can see how their teachings provide us with important resources needed for resolving philosophical problems that were originally undertaken by philosophers like the American Pragmatists John Dewey and Richard Rorty. When the pragmatists hoped to extirpate traditional metaphysics from moral philosophy, one of their focuses was on providing an alternative to the morality/prudence distinction. As this study illustrates, by overcoming the metaphysical dualism between the “unconditioned” and the “conditioned”, the Hongzhou Chan Buddhist can provide an account of compassion that is unconditionally grounded. Their account of compassion can then be understood as bridging the divide between “morality” and “prudence”.